Integration of qualitative and quantitative methods for land‐use‐change modeling in a deforestation frontier. Issue 6 (17th June 2022) - Siegel, Katherine; Farah Perez, Aldo; Kinnebrew, Eva; Mills‐Novoa, Megan; Ochoa, José; Shoffner, Elizabeth
Abstract: Development and implementation of effective protected area management to reduce deforestation depend in part on identifying factors contributing to forest loss and areas at risk of conversion, but standard land‐use‐change modeling may not fully capture contextual factors that are not easily quantified. To better understand deforestation and agricultural expansion in Amazonian protected areas, we combined quantitative land‐use‐change modeling with qualitative discourse analysis in a case study of Brazil's Jamanxim National Forest. We modeled land‐use change from 2008 to 2018 and projected deforestation through 2028. We used variables identified in a review of studies that modeled land‐use change in the Amazon (e.g., variables related to agricultural suitability and economic accessibility) and from a critical discourse analysis that examined documents produced by different actors (e.g., government agencies and conservation nonprofit organizations) at various spatial scales. As measured by analysis of variance, McFadden's adjusted pseudo R 2, and quantity and allocation disagreement, we found that including variables in the model identified as important to deforestation dynamics through the qualitative discourse analysis (e.g., the proportion of unallocated public land, distance to proposed infrastructure developments, and density of recent fires) alongside more traditional variables (e.g., elevation, distance to roads, and protection status) improved the predictive ability of these models. Models that included discourse analysis variables and traditional variables explained up to 19.3% more of the observed variation in deforestation probability than a model that included only traditional variables and 4.1% more variation than a model with only discourse analysis variables. Our approach of integrating qualitative and quantitative methods in land‐use‐change modeling provides a framework for future interdisciplinary work in land‐use change. Resumen: El desarrollo y la implementación de la gestión efectiva de las áreas protegidas para reducir la deforestación dependen parcialmente de la identificación de los factores que contribuyen a la pérdida del bosque y de las áreas en riesgo de ser convertidas, pero el modelado estándar del cambio de uso de suelo puede no capturar completamente los factores contextuales que no se cuantifican fácilmente. Combinamos el modelado cuantitativo del cambio de uso de suelo con el análisis cualitativo del discurso en un estudio de caso del Bosque Nacional Jamanxim de Brasil para entender de mejor manera la deforestación y la expansión agrícola en las áreas protegidas del Amazonas. Modelamos el cambio de uso de suelo entre 2008 y 2018 y lo proyectamos hasta 2028. Usamos las variables identificadas en una revisión de estudios que modelaron el cambio de uso de suelo en el Amazonas (p. ej.: variables relacionadas con la idoneidad agrícola y la accesibilidad económica) y en el análisis crítico del discurso que examinó documentos producidos por diferentes actores (p. ej.: agencias gubernamentales y organizaciones sin fines de lucro para la conservación) a varias escalas espaciales. Conforme a las medidas del análisis de varianza, la pseudo‐R2 ajustada de McFadden y el desacuerdo en la cantidad y la asignación, descubrimos que la inclusión dentro del modelo de las variables identificadas como importantes para las dinámicas de deforestación mediante el análisis cualitativo del discurso (p. ej.: la proporción de terrenos públicos sin asignar, la distancia hacia los desarrollos propuestos de infraestructura y la densidad de incendios recientes) junto con variables más tradicionales (p. ej.: elevación, distancia a las carreteras y estado de protección) mejoró la habilidad predictiva de dichos modelos. Los modelos que incluyeron la mezcla de variables explicaron hasta 19.3% más de la variación observada en la probabilidad de deforestación que un modelo que solamente incluyó las variables tradicionales y 4.1% más variación que un modelo con las variables del análisis del discurso. Nuestra estrategia de integrar los métodos cualitativos y cuantitativos dentro del modelado del cambio de uso de suelo proporciona un marco para futuros trabajos interdisciplinarios sobre el cambio de uso de suelo. 整合定性和定量方法进行森林砍伐边界的土地利用变化建模: 【摘要】制定和实施有效的保护区管理以减少森林砍伐, 部分取决于能否确定导致森林丧失的因素和面临土地转换风险的地区, 但标准的土地利用变化建模可能无法充分反映难以量化的背景因素。为了更好地了解亚马逊保护区的森林砍伐和农业扩张情况, 我们将定量的土地利用变化模型与定性的话语分析相结合, 对巴西Jamanxim国家森林进行了案例研究。我们模拟了2008‐2018年的土地利用变化情况, 并预测了到2028年的森林砍伐情况。本研究使用的变量来自一项对亚马逊地区土地利用变化建模研究的综述(如与农业适宜性和经济可及性相关的变量), 以及一项检验不同行为者(如政府机构和非营利性保护组织)在不同空间尺度上制定的文件的话语分析。通过方差分析、McFadden调整后的伪 R 2, 以及数量分歧与分配分歧的计算, 我们发现, 在模型中加入通过定性话语分析确定的森林砍伐动态的重要变量(如未分配的公共土地比例、与计划修建的基础设施的距离、近期火灾密度)以及更传统的变量(如海拔、与道路的距离、保护状态)可以提高这些模型的预测能力。包含话语分析变量和传统变量的模型与只包含传统变量的模型相比, 可解释的森林砍伐可能性的观测变异高19.3%, 而与只包含话语分析变量的模型相比高4.1%。我们在土地利用变化建模中定性和定量相结合的方法可以为未来土地利用变化的跨学科工作提供框架。【翻译:胡怡思;审校:聂永刚】